PERTAMBAHAN BIOMASSA IKAN NILA (Oreochromis niloticus) SELEKSI BAN NON SELEKSI DALAM KERAMBA JARING APUNG DI WADUK CIRATA DAN DANAU LIDO [Growth of selected and non selected Oreochromis niloticus in floating net cages in Grata Reservoir and Lido Lake] - Kusdiarti Kusdiarti; Ani Widiyati; Winarlin Winarlin; Rudhy Gustiano (Masyarakat Iktiologi Indonesia (Indonesian Ichthyological Society), 2008)
The objective of this study was to evaluate the result of selection program by comparing the growth of selected and non-selected fish. The study was carried out in floating net cages in Cirata Reservoir and Lido Lake, Each group of the examined fish used four cages 2x2x2m3 sized with densities of 300 fish in Cirata Reservoir and 225 fish in Lido Lake. Fish was fed 5% body weight a day with commercial pellet. Growth was observed by measuring the total biomass of every cage per three weeks. Results showed that selected fish has slightly bigger (26.0 ± 1.63) than non-selected one (23.0 ± 2.45) in Cirata Reservoir. For survival rate, selected fish has better performance (92 4 ± 0.01) than the non selected one (84,4 ± 0.05) in floating net cages in the Lido Lake (P < 0.01).